Comparative study on purposes and structure of Occupational Diseases Information System in America, Finland, French and Iran - R Safdari; N Masouri; O Aminian; S Davoodi (Tehran University of Medical Sciences, 2009)
Background and Aim: Occupational diseases are certain types of diseases that have been caused by special jobs and subject to special circumstances. There are several factors that can intensify these diseases. Various countries have indicated that they have played an effective role in decreasing exposures and its economic costs and attracting optimal resources through establishment of a comprehensive information system for occupational diseases with a appropriate structure. Health improvement is considered as the first aim of the health system which requires a comprehensive, complete and integrated information system on occupational disease. Materials and Methods: This is a descriptive Comparative study which was conducted in 2008 during which information systems in countries such as US, Finland, France and Iran have been studied based on their objectives and structures. Main instrument of this research was articles, books, magazines, valid internet sites in English language. Then, the gathered data were classified and analyzed. Results: All the three selected countries had an electronic information system and database in the field of occupational disease. In Finland, data of occupational diseases as well as their damages are kept in separate databases while US lacks a comprehensive system. There are countless systems in these countries in this field. In France, supervision on laboratories is a priority. In Iran, there is no certain comprehensive system for registering diseases. Discussion and Conclusion: All of these countries have the same objectives. Structure of occupational diseases information system, in Finland, is more comprehensive. Iran lacks such a system, so it is recommended to make use of the experiences of other countries and establish electronic comprehensive disease system in this country.